Narrowband, Visible-Blind UV-A Sensor Based on a Mg0.52Zn0.48O Film Deposited by Radio-Frequency Sputtering Using a ZnO-Mg Composite Target - Yuki Kohama; Takuya Nagai; Mitsuru Inada; Tadashi Saitoh (Advances in Materials Science and Engineering)
A narrowband, visible-blind ultraviolet photodetector (PD) for UV-A is fabricated using a Mg0.52Zn0.48O film that is formed on a quartz substrate by a radio-frequency sputtering technique using a ZnO-Mg composite target. The content of Mg in the film is controlled by varying the number of Mg chips on the ZnO plate. The fabricated PD has a metal-semiconductor-metal structure with interdigitated electrodes and exhibits a narrow 3 dB bandwidth of 26 nm with a peak response wavelength of 340 nm and a cut-off wavelength of 353 nm. Moreover, the peak responsivity of the PD increases linearly with the bias voltage up to 30 V, indicating that the device operates via a photoconductive gain mechanism.